Paint palette used by Iranian Masters based on Persian medieval recipes - Barkeshli, Mandana (K.G. Saur Verlag, 2013)
Classical Iranian literary sources contain valuable information with respect to materials and techniques related to the art of book-making, including pigments and dyes. Some of these writings have been composed in the form of mystical poetry which needs professional research into the language and classical terms used. Studying these primary sources is not only important for art historians but also for conservators and scientists to understand the material technology of the medieval Persian paint palette. These primary sources of knowledge in many occasions have led us to explore and reveal the secrets behind certain materials and techniques that were used during the medieval period and the reasons behind their usage. The present paper will discuss the Persian paint palette used in Persian manuscripts and miniature paintings from the 13th to 19th centuries.In this study, sixteen manuscripts have been selected and studied in detail; the recipe from each manuscript has been extracted according to each colour used in the Persian paint palette while the materials and techniques are also categorized and compared thoroughly. For easy reference, different materials and techniques used in each colour for preparation of the paint have been described separately with reference to the related treatises and their respective authors.